2022
DOI: 10.3389/fpls.2022.942875
|View full text |Cite
|
Sign up to set email alerts
|

TomatoDet: Anchor-free detector for tomato detection

Abstract: The accurate and robust detection of fruits in the greenhouse is a critical step of automatic robot harvesting. However, the complicated environmental conditions such as uneven illumination, leaves or branches occlusion, and overlap between fruits make it difficult to develop a robust fruit detection system and hinders the step of commercial application of harvesting robots. In this study, we propose an improved anchor-free detector called TomatoDet to deal with the above challenges. First, an attention mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Fruit detection from digital videos is based on computer vision and deep learning methods at present [39,41], which requires the use of computers and digital cameras instead of manual operations [5,7,10,11,17,28]. There are a lot of methods for fruit object detection [2,4,15,18,33]. The fruit detection essentially needs both classification and localization by providing the class labels and bounding box coordinates of the targets [8,14,16,26,27].…”
Section: Fruit Detectio Nmentioning
confidence: 99%
“…Fruit detection from digital videos is based on computer vision and deep learning methods at present [39,41], which requires the use of computers and digital cameras instead of manual operations [5,7,10,11,17,28]. There are a lot of methods for fruit object detection [2,4,15,18,33]. The fruit detection essentially needs both classification and localization by providing the class labels and bounding box coordinates of the targets [8,14,16,26,27].…”
Section: Fruit Detectio Nmentioning
confidence: 99%
“…It is not limited to the influence of the object scale feature in the training data during prediction to avoid the shortcoming of the lack of flexibility in the generation of bounding boxes. Several scholars [ 31 – 34 ] have already applied the anchor-free detector for fruit detection. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. [ 31 ] proposed TomatoDet for tomato detection, which avoids the complex hyperparameter design and low detection efficiency caused by exhaustive anchor boxes and classification operations in anchor-based detectors. However, the circular bounding boxes generated by this model are only suitable for tomatoes or other round fruits with aspect ratios close to 1:1, not for other species with substantial differences in aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies mainly reported the use of the following frameworks: early single-shot models, such as YOLO v3 [18,19] and SSD [3,20]; and double-shot models, such as faster RCNN [2,21] and Mask RCNN [1,22]. In addition to using state-of-the-art deep learning architectures in 2022 and beyond, research on improving parts of the network and optimizing it for tomato detection has become a central concern for researchers; YOLO v4 [20,23,24], YOLO v5 [25,26], YOLO X [27], YOLO v8 [28], and CornerNet [29].…”
Section: Introductionmentioning
confidence: 99%